Volitive interjections in Langkat Malay - Mulyadi; Mahriyuni; Maharani, Mifta Huljannah (Center of Language and Cultural Studies [CLCS], 2023)
This study describes the categorization of volitive interjections in Langkat Malay based on meaning and form. The purpose of this research is to describe or classify volitive interjections in Langkat Malay. The method used is qualitative. The source of the data came from written data in the form of writings in Langkat Malay contained in Langkat Malay books and oral data obtained from informants, namely Langkat Malay speakers. The data collection method used is the see method. The results of the study found 21 types of emotive interjections in Langkat Malay, namely moh,tuh, nah, mih, oi, woi, heei, o, cop, shhh, stt, heh, hus, hey, hai, wahai, duhai, ker.. ker, ri..ri, ck..ck, and hush..hush. In general, there are 5 types of semantic components that serve as a reference for classifying emotive interjections in Langkat Malay, namely I want someone to do something, I want someone to know something, I don't want someone to do something, I don't want someone to say something, I want this animal. do something.